Pengaruh Bed Temperature Dan Print Speed Pada Proses Fdm Menggunakan Filamen Polypropelene Terhadap Kuat Tarik - Idola Brilian; Idiar Idiar; Pristiansyah Pristiansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
The experimental results demonstrate that bed temperature and print speed exert significant effects on the tensile strength of polypropylene components produced via FDM. An increase in bed temperature consistently improves tensile performance, with the optimal strength obtained at 75°C. Higher bed temperatures promote stronger interlayer diffusion and reduce residual thermal stress. In contrast, increasing print speed generally leads to a decline in tensile strength due to limited bonding time and the formation of voids within the printed structure. The combination of high bed temperature and low print speed yields the most favorable mechanical properties. Overall, the study confirms that precise control of thermal and kinetic parameters is essential for enhancing the mechanical integrity of polypropylene parts manufactured through the FDM process.